Diversité alimentaire et prééminence du riz dans les habitudes de consommation au Cameroun - Sariette Batibonak (Éditions en environnement VertigO, 2015)
Cameroon has a natural potential under tapped. Dozens of plant foods provide evidence of the importance of its resources. The richness of its forests and lands is attested by various studies. Despite this wealth of food resources, only fifteen are part of the people's food choices. However, for decades, it is clear that people primarily use rice, neglecting other food resources available. How to understand those inclined to consume mainly agricultural rice products? Through this paper, we sketch a paradox between this potential food resources and the people’s choice brought to the consumption of rice in a context of changing eating habits. By an anthropological approach, reflection leads to the conclusion that Cameroonian households carry their sights, primarily on rice products.